Genome Sequence of Lactococcus garvieae UNIUD074, Isolated in Italy from a Lactococcosis Outbreak - Reimundo, Pilar (American Society for Microbiology, 2011)
Lactococcus garvieae is the etiological agent of lactococcosis disease, affecting many cultured fish species worldwide. In addition, this bacterium is currently considered a potential zoonotic microorganism since it is known to cause several opportunistic human infections. Here we present the draft genome sequence of the L. garvieae strain UNIUD074.